استخدام تكنولوجيا الاتصال في التعليم الالكتروني - نبار, ربيحة; مقاوسي, كريمة (جامعة الوادي - University of Eloued, 2022)
ملخص: تهدف هذه الدراسة الى التعرف على التعليم الالكتروني واستخدامه في التعليم، خاصة في العصر الحالي الذي يتميز بالتغير والتطور السريع والمستمر، بحيث تتزايد المعلومات وتتنوع أشكالها وتختلف مصادرها، مما انعكس على التطور بمختلف مناحي الحياة وفى مقدمتها التعليم، والذي يشكل الأساس والعمود الفقري في بناء المجتمعات و تكوين الفرد وبلورة ملامحه،ويعتبر التعليم الإلكتروني من أحدث الأنظمة في مجال التعليم لما يتميز به من إمكانيات هائلة في دعم وتطوير العملية التعليمية، وابتكار سبل جديدة للتعليم والمساهمة في تحقيق التعليم وبلوغ الأهداف التربوية، وتمكين المتعلمين من الاستقلالية والحرية عند البحث عن المعلومات،وكذلك لما يتميز به من إمكانية إيصال العملية التعليمية للجميع، متخطيا حواجز الزمان والمكان، وزيادة كفاءة التعليم الذي يعد استثمارا بشريا له مدخلاته وعملياته ، وبالتالي تمكين الفرد من المساهمة في تنمية مجتمعه وتطويره. Abstract: This study looks to identify e-learning and its use in education, especially in the current era that is by rapid and continuous change and development, so that information increases, its characterized forms vary and its sources differ, which is reflected in the development in various walks of life, especially education, which forms the basis and the backbone in building societies And the e-learning is considered one of formation of the individual and the crystallization of his features, the most recent systems in the field of education because of its tremendous potential in supporting and developing the educational process, innovating new ways of education and contributing to the achievement of education and achieving educational goals, and enabling learners to be independent and free when searching for information, as well as for its ability to communicate The educational process for all, bypassing the barriers of time and space, and increasing the efficiency of education, which is a human investment with its inputs and processes, thus enabling the individual to contribute to the development and development of his society.
مقال
Keywords: تكنولوجيا ؛ تعليم؛ تكنولوجيا المعلومات والاتصالات؛ تكنولوجيا التعليم؛ تعليم إلكتروني; technology; education; information and communication technology ; educational technology,-e -learning